Investment Strategies and Portfolio Management of Sharia Equity Mutual Funds under Macroeconomic Uncertainty in Indonesia - Sisca Debyola Widuhung; Sunarmo Sunarmo (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Macroeconomic uncertainty, characterized by inflation fluctuations, interest rate changes, exchange rate volatility, and slowing economic growth, poses a major challenge to the management of Islamic equity mutual funds in Indonesia. This study aims to analyze investment strategies and portfolio management of Islamic equity mutual funds in the face of economic instability. The study employed a descriptive qualitative approach with documentation techniques through analysis of fund fact sheets, mutual fund performance reports, official publications, and various relevant previous studies. The results indicate that a diversification strategy across sectors and financial instruments, the selection of Islamic stocks based on strong fundamentals, and portfolio composition adjustments through rebalancing are key strategies for maintaining portfolio stability. Furthermore, Islamic principles have been proven to serve not only as an ethical foundation for investment but also as a risk management mechanism by limiting investment in speculative and high-risk sectors. This study concludes that the management of Islamic equity mutual funds requires an adaptive, selective, and long-term-oriented strategy to maintain investment stability amidst economic uncertainty. These findings provide implications for investors, investment managers, and regulators in strengthening the resilience of the Islamic financial industry in Indonesia.